Cultural bandwagon to cultural brand-wagon: a study of the cultural branding and influence of culture-led urban regeneration and city branding on resident arts organisations in Newtown, Johannesburg - Virasamy, Bernadia (My University, 2010)
Culture-led urban regeneration has proved problematic over the years. Often, due to the transitory nature of the culture, the brand remains but the culture has evolved. This study has, through the use of qualitative research methodology, focused on the cultural branding of the Newtown Cultural Precinct and its impact upon the resident arts and culture organisations there. The data was analysed using a variation of themes which emerged through the interview and data analysis process. These ranged from perceptions of the brand to an exploration of relationships among stakeholders in the Precinct. It was clearly seen here that a non-consultative approach has opened up several avenues for miscommunication and misunderstanding in Newtown resulting in tensions that could have easily been avoided. Looking at Arenstein’s (2006) Ladder of Participation it could be seen that consultation and participation by all parties was not embarked upon and this had led to further mistrust. A closer look at the brand of the Newtown Cultural Precinct and the stakeholders show that relationships need to be fostered around brand construction and implementation, marketing and participation in brand promotion. There are no innocent bystanders here as each and every stakeholder is responsible for the success of the brand and no single party should drive it but through joint efforts the brand could be functional and effective. Recommendations are made to both promote and strengthen the brand and it is envisaged that some of these would be implemented by relevant authorities so as to ensure the longevity of the brand of the Newtown Cultural Precinct.